THE EFFECT OF EXCESSIVE SMARTPHONE USE ON MENTAL WELLBEING, SLEEP QUALITY AND ACTIVE LIFESTYLE BEHAVIOURS - Hamerla, Anna; Gawron, Julia; Szydłowski, Radosław; Bodera, Magdalena; Porwolik, Hanna; Hamerla, Dominika; Czarnecki, Bartłomiej; Kaźmierska, Anna; Grajcarek, Łukasz (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Mobile phone addiction has become a very common phenomenon among young people. It leads to a number of negative consequences for their health, both physical and mental. The aim of this paper is to present the most important consequences of excessive phone use in terms of mental health, such as depression, anxiety and feelings of loneliness. Issues such as the impact of phone addiction on sleep disorders, orthorexia and eating behaviour are also discussed. The paper highlights that excessive use of mobile devices can significantly affect the quality of life of young people, contributing to emotional disturbances and reduced psychological well-being. Conclusions point to the need for further research and educational activities to reduce the negative impact of this phenomenon. Methodology: For this work, we conducted a search in the PubMed and Google Scholar databases using the keywords: "phone addiction," " health," " lifestyle," " mental wellbeing" followed by an analysis of the selected materials. Aim of the study: The aim of this work is to analyse the impact of smartphone addiction on young people’s mental health, with a focus on aspects such as depression, anxiety, sleep disorders, orthorexia, social relationships and feelings of loneliness. Conclusion: Excessive use of mobile devices can have a significant impact on the quality of life of young people, contributing to emotional, sleep and eating disorders. Preventive measures are advisable, including education on sleep hygiene, limiting the time spent in front of screens before bedtime and promoting healthy lifestyles among young people and students.